Application Of Restorative Justice In The Settlement Of Corruption Crimes - Ilham Nur Pratama; Nurul Restu Azyanti (Faculty of Law, Universitas Lampung, 2022)
Corruption is a problem that is detrimental to state finances. The magnitude of the handling of corruption cases and the handling of the investigation process to execution will not be comparable if the corruption has a slight state loss. Unlike the punishing justice method with the current developments, it makes legal decisions on state losses with the restorative justice method against minor corruption crimes. Using the juridical-normative method, the authors look for available data on the mechanism and its implementation and the implementation of restorative justice by the High Court in the Lampung Province Regions. This research's problem discussed criminalizing corruption from the perspective of restorative justice and how an advocate can apply the concept of restorative justice to corruption in Lampung area. The results show that Restorative justice is an alternative for resolving corruption cases because it provides a comprehensive and effective solution for retributive justice needs to fulfill the goal, namely the non-optimal return of state financial losses. The concept of state restorative justice as a public representative is realized only to punish the perpetrators (retributive justice).